Clinical and survival of patients with multiple myeloma in a state of Northeast Brazilian - Ferreira, Kalyane da Silva; Azevedo, Isabelle Campos de; Maciel, James Farley Rafael; Carvalho, Diana Paula de Souza Rego Pinto; Vitor, Allyne Fortes; Ferreira JÃºnior, Marcos Antonio (Revista Cubana de Hematología, Inmunología y Hemoterapia, 2017)
Introduction: The annual prevalence of Multiple Myeloma in patients aged between 65 and 74 years old is 31 cases for every 100 000 people and increases to 46 cases per 100 000 people in patients older than 75 years old. Objectives: To clinically characterize patients with multiple myeloma treated at a referral center in the state of Rio Grande do Norte, Brazil, and to estimate their survival. Methods: Retrospective cohort study. For data collection, secondary sources listed in the cadastral database and complementation with data records was used. The descriptive analysis was performed by using the Epi Info program, version 3.5.2 and the survival analysis used Statistic Package for Social Sciences (SPSS) software version 22. Results: Out of the 39 patients studied, 17 (43.6%) were male, and 22 (56.4%) were female, with an average age of 66.3 years old. The main medication therapeutic regimen was the combination of Cyclophosphamide, Thalidomide, and Dexamethasone (CTD), as the most medical prescription used in 63.6% of cases. Only 38.5% had other comorbidities and 46.2% of patients developed plasmacytoma. In the International Staging System (ISS), stage III prevailed with 30.8% among the evaluated patients. The cumulative probability of global survival rate showed a disease with a survival rate of 50% of the sample in about 36 months (three years) after diagnosis is confirmed.